2020
DOI: 10.1016/j.brs.2020.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Paired Associative Stimulation drives the emergence of motor resonance

Abstract: Background: Associative plasticity, the neurophysiological bases of Hebbian learning, has been implied in the formation of the association between sensory and motor representations of actions in the Mirror Neuron System; however, such inductor role still needs empirical support. Objective/hypothesis: We have assessed whether Paired Associative Stimulation (PAS), known to activate Hebbian associative plasticity, can induce the formation of atypical (absent in normal conditions), visuomotor associations, reshapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…Experiments that were designed to isolate the kind of learning involved in mirror neuron development have suggested that sensorimotor learning is crucial (Catmur et al, 2011;de Klerk et al, 2015;Press et al, 2012a;Fitzgibbon et al, 2016;Guidali et al, 2020;Wiggett et al, 2012). For example, replicating and extending earlier work with a similar design (e.g.…”
Section: Sensorimotor Learningmentioning
confidence: 96%
See 1 more Smart Citation
“…Experiments that were designed to isolate the kind of learning involved in mirror neuron development have suggested that sensorimotor learning is crucial (Catmur et al, 2011;de Klerk et al, 2015;Press et al, 2012a;Fitzgibbon et al, 2016;Guidali et al, 2020;Wiggett et al, 2012). For example, replicating and extending earlier work with a similar design (e.g.…”
Section: Sensorimotor Learningmentioning
confidence: 96%
“…In the last decade, more evidence has emerged that learning plays an important role in the development of mirror neurons (Brunsdon et al, 2019;Catmur et al, 2011;Copete et al, 2016;de Klerk et al, 2015;Fitzgibbon et al, 2016;Furukawa et al, 2017;Guidali et al, 2020;Hou et al, 2017;McKyton et al, 2017;Orlandi et al, 2017;Press et al, 2012a;Wiggett et al, 2012;Zazio et al, 2019).…”
Section: Sensorimotor Learningmentioning
confidence: 99%
“…In the past decade, more evidence has emerged that learning plays an important role in the development of mirror neurons ( Brunsdon et al, 2020 ; Catmur et al, 2011 ; Copete et al, 2016 ; de Klerk et al, 2015 ; Fitzgibbon et al, 2016 ; Furukawa et al, 2017 ; Guidali et al, 2020 ; Hou et al, 2017 ; McKyton et al, 2018 ; Orlandi et al, 2017 ; Press et al, 2012 ; Wiggett et al, 2012 ; Zazio et al, 2019 ). Some of the recent studies have reported greater activity in mirror-neuron brain areas in pianists and dancers than in people who lack such expertise during observation of musical performance and dance, respectively ( Furukawa et al, 2017 ; Hou et al, 2017 ; Orlandi et al, 2017 ).…”
Section: Originsmentioning
confidence: 99%
“…By varying the inter-stimulus interval (ISI) between these stimulations, PAS protocols can affect synaptic plasticity, inducing long-term potentiation (LTP)-like and depression (LTD)-like after-effects on cortical excitability [i.e., Spike-timing-dependent plasticity (STDP); e.g., Caporale and Dan, 2008] in the stimulated cortical area or circuit (e.g., Stefan et al, 2000;Wolters et al, 2003). Over the last 2 decades, PAS literature moved from the widely replicated, classical protocol, pairing electric stimuli with M1-TMS (i.e., M1-PAS), to more complex protocols targeting sensory and crossmodal networks (e.g., Wolters et al, 2005;Schecklmann et al, 2011;Suppa et al, 2013Suppa et al, , 2015Sowman et al, 2014;Ranieri et al, 2019;Zazio et al, 2019;Guidali et al, 2020). Overall, these peripheral-cortical protocols proved to be robust and flexible tools to non-invasively investigate and interact with the plastic properties of sensorimotor networks in humans (for a review, see: Carson and Kennedy, 2013;Suppa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%